A Supported Ni Catalyst Produced from Ni‐Al Hydrotalcite‐Like Precursor for Reduction of Furfuryl Alcohol to Tetrahydrofurfuryl Alcohol by NaBH4 in Water. Issue 4 (21st January 2021) - Ren, Dezhang; Wang, Jingyi; Jiang, Xuelei; Song, Zhiyuan; Norinaga, Koyo; Huo, Zhibao
Abstract: Tetrahydrofurfuryl alcohol (THFA) is a kind of high value‐added compound in industry, which can be obtained from biomass chemical engineering. However, Synthesis of THFA under mild condition with green hydrogen donors remains a big challenge. In this article, a supported Ni catalyst derived from Ni−Al hydrotalcite‐like compounds (HTs) as precursors for the reduction of furfuryl alcohol (FA) into THFA with NaBH4 as reducing agent in water was first reported. As a result, Ni/Al2 O3 −HT exhibited high catalytic activity for the transformation, and THFA was achieved in 100 % yield at 60 °C for 60 min. Moreover, Ni/Al2 O3 −HT could be recycled at least seven times without the loss of its activity. Under optimized conditions, the reduction reaction of several furan and ketone compounds was investigated. A possible mechanism for the reduction of FA to afford THFA was also proposed. Abstract : A supported Ni catalyst produced from Ni−Al hydrotalcite‐like precursor for reduction of furfuryl alcohol to tetrahydrofurfuryl alcohol by NaBH4 in water. NaBH4 display good promise as reducing agent for the reduction of furan ring. Under the optimal conditions, the combination of Ni/Al2 O3 −HT and NaBH4 has good performance not only in reducing furan ring, but also in reducing ketones and benzene ring.